The Online STEM Classroom—Who Succeeds? An Exploration of the Impact of Ethnicity, Gender, and Non-traditional Student Characteristics in the Community College Context. (April 2015) - Wladis, Claire; Conway, Katherine M.; Hachey, Alyse C.
Objective: This study analyzes how ethnicity, gender, and non-traditional student characteristics relate to differential online versus face-to-face outcomes in science, technology, engineering, and mathematics (STEM) courses at community colleges. Method: This study used a sample of 3, 600 students in online and face-to-face courses matched by course, instructor, and semester from a large urban community college in the Northeast. Outcomes were measured using rates of successful course completion (with a "C−" or higher). Multilevel logistic regression and propensity score matching were utilized to control for unobserved heterogeneity between courses and for differences in student characteristics. Results: With respect to successful course completion, older students did significantly better online, and women did significantly worse (although no worse than men) online, than would be expected based on their outcomes in comparable face-to-face courses. There was no significant interaction between the online medium and ethnicity, suggesting that though Black and Hispanic students may do worse on average in STEM courses than their White and Asian peers both online and face-to-face, this gap was not increased by the online environment. Contributions: These findings suggest that both women and younger students in STEM courses may need extra support in the online environment. Future research is needed (a) to explore whether factors such as stereotype threat or child care responsibilities affect the outcomes of women in online STEM courses, and (b) to determine which characteristics (e.g., motivation, self-directed learning skills) of older students may make them particularly well suited to the online environment.